Myelopathy: A Clinical Approach - Bhai, Salman; Bhattacharyya, Shamik (Seminars in Neurology, 2021)
Myelopathy is a clinical diagnosis with many causes. A focused history and neurologic exam can help identify a myelopathic syndrome that guides a targeted workup. Though an exact cause may not always be identified, a thoughtful clinical approach can narrow down the differential diagnosis enough to treat the patient.
Keywords: myelopathy; spinal cord anatomy; spinal cord localization